2016
DOI: 10.1016/j.qref.2015.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Does style-shifting activity predict performance? Evidence from equity mutual funds

Abstract: Available online xxx JEL classification: G11 G20 G23 a b s t r a c tThis study introduces an innovative approach to measuring the "style-shifting activity" (SSA) of mutual funds using daily returns. Applying our new measure to a comprehensive sample of 2631 active US equity mutual funds, we show (i) that SSA predicts future performance, especially for current outperformers, and (ii) that SSA adds new information previously not captured by alternative return-based activity measures such as tracking error or R-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 67 publications
1
11
0
Order By: Relevance
“…Our results confirm the findings of Cao et al (2017) in the case of the fund size, and of Herrmann et al (2016) in the case of the one-month lagged return. The other results concerning other characteristics that we found essential to the classification of openend investment funds based on the standard deviation seem to be pioneering.…”
Section: Other Characteristics Essential To Fund Classificationsupporting
confidence: 90%
“…Our results confirm the findings of Cao et al (2017) in the case of the fund size, and of Herrmann et al (2016) in the case of the one-month lagged return. The other results concerning other characteristics that we found essential to the classification of openend investment funds based on the standard deviation seem to be pioneering.…”
Section: Other Characteristics Essential To Fund Classificationsupporting
confidence: 90%
“…It is helpful in recognizing the investment preferences across sectors, countries (Parikh 2019), and investment characteristics (Kaiser 2020). This is useful to compare styles across different funds' types like equity (Herrmann et al 2016), fixed income (Hou et al 2019), and alternative investments [ (Weng and Trück 2011;Chevalier and Darolles 2019)].…”
Section: Investment Styles During Pandemicmentioning
confidence: 99%
“…Galloppo (2017) showed that company fundamentals do not have significant effects on style drift in US equity funds. Herrmann (2016), using monthly returns data on 2631 US equity funds between October 1998 and December 2009, found that a fund's style shifting activity, measured as the difference between multi-factor regression betas from two consecutive quarters, is a useful measure of a fund's performance. Kurniawan (2016) investigated the relationship between fund governance and style drift in US mutual funds and reported that the effectiveness of fund governance is negatively related to a fund's style drift; further, funds whose managers have more decisionmaking power are more likely to exhibit style drift than those whose owners are independent from the managers.…”
Section: Literature Reviewmentioning
confidence: 99%